Prodensa Consulting Services: in search of corporate entrepreneurs. Issue 4 (7th November 2022) - Ghura, Amarpreet Singh; DeNoble, Alex; Martínez Flores, Raúl
Abstract : Learning outcomes: Discussion of the case will enable students to: explain what are the five specific dimensions that are important determinants of an environment conducive to entrepreneurial behavior; analyze how to measure the internal environment on the five dimensions critical to creating an entrepreneurial/innovative environment; devise a profile of the firm across the five dimensions – top management support, work discretion, rewards and reinforcement, time availability and organizational boundaries; explain how to attempt to identify the perceived gaps at the unit or division level and then work to rectify the specific areas; and describe models of corporate entrepreneurship. Case overview/synopsis: Mexicali is a border city in the state of Baja California, Mexico. It was in the month of May 2022. The President of Prodensa Consulting Services (PCS), Marco Kuljacha (Marco), was sitting in his office thinking about a way forward to create an intrapreneurial culture by identifying more "Marcos or Marcias" among his current PCS employees. As he contemplates the future of the company, he is hoping to identify individuals within the organization who exhibit an entrepreneurial mindset through generating and leading new business initiatives for PCS. He desires to support people who have the potential to emerge as future leaders within the organization. He is striving to identify those individuals who want to proactively develop their career trajectories in ways similar to Marco's earlier professional experiences. After starting with Grupo Prodensa in 2006 as a Junior Project Manager, Marco, by pursuing an intrapreneurial path, worked his way up to become President of the PCS in 2022. According to Marco, such individuals should exhibit the willingness to foster opportunities for new business ventures for PCS and possess traits such as innovation, proactivity, risk-taking, accountability and networking. With an eye toward the need for continuous innovation and change, Marco was thinking about ways to identify and develop entrepreneurially minded individuals among his employees working at PCS. Corporate entrepreneurship was of great importance for him and the future of the company. The case provides an opportunity for students to step into the shoes of Marco and find an appropriate intrapreneurship model to implement the intrapreneurship culture. In doing so, students should take into consideration the data regarding the existing corporate entrepreneurship processes and teams at Grupo Prodensa that helped it to innovate and make assumptions to analyze the feasibility of implementing intrapreneurship culture by finding more Marco or Marcia. Complexity academic level: This case can be used as an introductory case in a postgraduate class on corporate entrepreneurship, as it delineates the challenges faced by Marco in finding an appropriate intrapreneurship model and finding in PCS more Marco or Marcia has qualities such as innovator, proactive, risk-taker, accountability, networking, for implementing corporate entrepreneurship culture in PCS. The case can also be used in a corporate entrepreneurship course and an innovation management course. The case allows students to learn about the model of corporate entrepreneurship; strengths, opportunities, aspirations and results analysis; pros and cons analysis; and challenges faced by the company during the implementation of corporate entrepreneurship. Thus, the case can be used for covering multiple perspectives related to measuring the internal environment or managers' perception of the five dimensions critical to implementing corporate entrepreneurship (e.g. the application of the Corporate Entrepreneurship Assessment Instrument), and is ideal for teaching the different corporate entrepreneurship models. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 3: Entrepreneurship.